(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
The insertion reactions of 1CH2, 1CHF and 1CF2Â into 1o and 2o polar O-H bonds of methanol, ethanol, 1-propanol and 2-propanol have been investigated at ab initio (HF, MP2) and DFT levels using 6-31g (d, p) basis set. In the two-step mechanism of carbene insertion into O-H bond, initially the reactants form an ylide-like complex, which then undergoes the 1, 2-proton shift concertedly giving the ether product. The barrier heights of the TSs in the concerted mechanism vary with the type of carbene and the O-H bond. Frontier orbital energies (FOE) indicate that the initial interactions between the alcohols and carbenes are controlled mainly by the HOMO of alcohols and the LUMO of carrbenes. This fact is substantiated by NBO charge analysis, which indicates the net amount of charge transfer from alcohol to carbene moiety in the transition states at B3LYP (MP2)/6-31g (d, p) levels.Â